Multiliteracies: Life of an Idea - Kalantzis, Mary; Cope, William (The international journal of literacies, 2023)
Several decades have now passed since the publication in the Harvard Educational Review of the article by the New London Group, “A Pedagogy of Multiliteracies: Designing Social Futures” (1996). Published on the cusp of a revolution in our means of production of meaning, the article proved to be one of the most influential in the field of literacy education. Looking back over these decades, the article that follows is an intellectual biography written by two members of the original New London Group. It traces the origins of the idea, the subsequent work of the members of the group, and the main contours of the idea as reflected in a review of the literature.